The potential of Arachis pintoi biomass to improve quality of soil continuously used for cassava cropping - N Muddarisna; S Prijono (Brawijaya University, 2014)
A field experiment that was aimed to elucidate the effects of application of Arachis pintoi biomass and animal dung on quality of soil continuously used for cassava cropping was conducted at Jatikerto Village, Kromengan District of Malang Regency. Eight treatments tested were 100% NPK inorganic fertilizer, 100 kg N Arachis pintoi/ha, (3) 100 kg N chicken dung / ha, 100 kg N cow dung /ha, 100 kg N goat dung /ha, 100 kg N Arachis pintoi + chicken dung /ha, 100 kg N Arachis pintoi + cow dung /ha, and 100 kg N Arachis pintoi + goat dung /ha. Monitoring quality of top soil (0-20 cm) was carried out at planting time and 3 months after planting. Soil samples were collected and analyzed for chemical and physical properties. Yield of cassava was measured at 6 months after planting. Results of this study showed that application of organic fertilizer in forms of green manure (Arachis pintoi biomass), and animal dung significantly improved physical and chemical properties of soil. Application of 50% NPK combined with organic manures did not significantly gave different tuber yield with that of 100% NPK.